(2m-3n)square-(2m+3n)square
Answers
Answered by
4
hey...
(2m-3n) ^2 = (2m)^2 + (3n)^2 - 2(2m)(3n)
= 4m^2 + 9n^2 - 12mn ...... (1)
(2m+3n)^2 = (2m)^2 + (3n)^2 + 2(2m)(3n)
= 4m^2 + 9n^2 + 12mn..... (2)
(1) - (2)
= 4m^2 + 9n^2 - 12mn - 4m^2 - 9n^2 -12mn
= -24mn
(2m-3n) ^2 = (2m)^2 + (3n)^2 - 2(2m)(3n)
= 4m^2 + 9n^2 - 12mn ...... (1)
(2m+3n)^2 = (2m)^2 + (3n)^2 + 2(2m)(3n)
= 4m^2 + 9n^2 + 12mn..... (2)
(1) - (2)
= 4m^2 + 9n^2 - 12mn - 4m^2 - 9n^2 -12mn
= -24mn
Answered by
1
Attachments:
![](https://hi-static.z-dn.net/files/d19/fd41aedd27be694aed9ea89980d11c87.jpg)
Similar questions